Application of Trichoderma sp. and PGPR for preventing downy mildew incidence on sweet corn - Purwanti, Eny Wahyuning; Wahyudi, Diki; Hamyana (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Downy mildew is a disease caused by the fungus Peronosclerospora maydis. Application of biological agents to control downy mildew is a kind of environmentally friendly control method, that widely promoted recently. Trichoderma sp. and plant growth promoter rhizobacteria (PGPR) are root symbionts, which can induce plant resistance against disease infection. This study aimed to determine the effective application of Trichoderma sp. combined with various concentrations of rhizobacteria to control downy mildew. This study used a completely randomized design (CRD) method with 6 treatments and 5 replications. The treatment was the concentration of rhizobacteria consisting of P0 (control) = without treatment, P1= 15 mL L-1. P2 = 30 mL L-1. P3 = 45 mL L-1. P4 = 60 mL L-1 and P5 (positive control) = seed treatment with 5 g kg-1 dimetomorf fungicide. Each rhizobacteria suspension was mixed with Trichoderma sp. solution as much as 15 mL L-1. The parameters observed consisted of plant height (cm), number of leaves, disease incidence (%), and disease severity (%). The results showed that the combination of Trichoderma sp. and rhizobacteria of 60 mL L-1 was able to inhibit the incidence of the disease up to 66.53% and the severity of the disease up to 89.84%. Keywords: bacteria, concentration, downy mildew, sweet corn, Trichoderma sp.